CRITERION ANALYSIS OF CLOUD-BASED TOOLS IN DATABASE BASICS TRAINING - Golubeva, Tatyana; Linder, Natalia; Zoidov, Kobilzhon; Petrov, Vladislav; Maximov , Denis; Abdulkadirov, Umalt (Revista Inclusiones, 2020)
The formation and development of an educational environment on the basis of cloud computing technology is an urgent area in the modern renewal of higher education. It is associated with the spread of more convenient systems for organizing access to electronic resources and services, the possibilities of teamwork with software applications. The article presents an analysis of studies on various aspects of the use of cloud-based tools in the educational process. Based on the results of the expert survey, the ranking and selection of the most acceptable cloud-based training tools for teaching the database basics were carried out. The study defines the criteria and indicators for the selection of cloud-based tools, on the basis of which a criteria-based analysis of cloud-based tools was carried out when teaching the basics of databases. It is concluded that the introduction of cloud-based tools into the educational process of teaching the basics of databases is necessary on the basis of compliance with the functional and didactic and organizational criteria.